(untitled) (AYUSHDHARA, 2021)
The disease Amavata described in classical Ayurvedic literature is closely mimic with Rheumatoid Arthritis (RA) in modern medical science. Amavata is the challenging problem for medical science with different treatment protocol. In this clinical study 15 patients were included having typical symptoms. All the included patients treated with Vaitaran Basti (medicated enema) to evaluate its efficacy in said disease. The patients were diagnosed on the basis of American criteria of Rheumatoid Arthritis as well as signs and symptoms mentioned in the classics. Aim: To assess the efficacy of Vaitaran Basti in the patients of Amavata, reveal the probable action of Vaitarana Basti in the management of Amavata. Materials and Methods: In the present study 15 patients of Amavata were studied. These patients were selected irrespective of sex, religion and economical status. The patients were diagnosed on the basis of American criteria of Rheumatoid Arthritis as well as signs and symptoms mentioned in the classics. American is mentioned criteria of Rheumatoid. Result: Paired t test was applied to this BT and AT scores as these grades are accepted as per international norms. It showed that administered therapy reduced degree of disease activity significantly as P < 0.001. Conclusion: It showed that administered therapy reduced degree of disease activity significantly as P < 0.001.